Excavation of komořany tunnel in sand: a case study (2023)
This paper presents a study of the accuracy of two-dimensional (2D) finite-element predictions of a displacement field of retaining structures supporting the excavation next to the Komořany tunnel in Prague, Czech Republic. The ground material is a Komořany sand, which is a sand with some gravel and almost no fines. Two different constitutive models were used to represent the mechanical behavior of Komořany sand, namely the standard Mohr–Coulomb model and a hypoplastic model for sands with intergranular strain. High-quality laboratory investigation was performed and used for calibrating the model parameters. In addition, good-quality displacement field measurements were used as a benchmark for the models’ predictions. The simulation results suggest that the hypoplastic model predicts both the laboratory and field measurement results with more accuracy. A discussion about the importance of the correct selection of the constitutive model on the prediction of boundary value problems is also presented.